Coordination‐Driven Macrocyclization for Locking of Photo‐ and Thermal cis→trans Isomerization of Azobenzene. Issue 49 (8th October 2014) - Yamamura , Masaki; Yamakawa, Koji; Okazaki, Yuki; Nabeshima , Tatsuya
Abstract Both trans and cis isomers of azobenzene‐linked bis‐terpyridine ligand L1 were incorporated in rigid macrocycles linked by FeII(tpy)2 (tpy: terpyridine) units. The complex of the longer trans‐L1 is dinuclear [(trans‐L1)2⋅FeII2], whereas the complex of the shorter cis‐L1 is mononuclear [cis‐L1⋅FeII]. The complex cis‐L1⋅FeII was not only thermally stable but also photochemically inactive. These results indicate a perfectly locked state of cis‐azobenzene. The stable macrocyclic structure of cis‐L1⋅FeII causes locking of the isomerization. To the best of our knowledge, this is first example of dual locking of photo‐ and thermal isomerization of cis‐azobenzene.